Approximate symmetries in the Interacting Boson Model - Bonatsos, D. (HNPS Advances in Nuclear Physics, 2019)
Dynamical symmetries have played a central role for many years in the study of nuclear structure. Recently, the concepts of Partial Dynamical Symmetry (PDS) and Quasi-Dynamical Symmetry (QDS) have been introduced. We shall discuss examples of PDS and QDS appearing in the large boson number limit of the Interacting Boson Mod